2022
DOI: 10.1108/ci-11-2021-0221
|View full text |Cite
|
Sign up to set email alerts
|

Interface management of offsite bathroom construction: a conceptual model

Abstract: Purpose This paper aims to identify and discuss how process and people factors influence the successful implementation of organisational interface management in offsite bathroom construction. Design/methodology/approach A literature review identified 16 process and people factors. A mixed method approach was used to analyse data from eight offsite bathroom case study projects. A ranking approach determined the main process and people factors, consequently analysed using (Minitab) Frequency analysis, the Wilc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…For example, Gibb, G.F. explored the influencing factors of organizational interface management in PBPs from the perspective of people and process. The results showed that early intervention of contractors and open communication among stakeholders was critical to solving organizational interface problems [26]. To address the challenges faced by offshore oil and gas projects in terms of schedule and cost, Nooteboom, U. proposed an interface management approach.…”
Section: Pbps Interface Management Influencing Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Gibb, G.F. explored the influencing factors of organizational interface management in PBPs from the perspective of people and process. The results showed that early intervention of contractors and open communication among stakeholders was critical to solving organizational interface problems [26]. To address the challenges faced by offshore oil and gas projects in terms of schedule and cost, Nooteboom, U. proposed an interface management approach.…”
Section: Pbps Interface Management Influencing Factorsmentioning
confidence: 99%
“…Since prefabricated components or parts are difficult to change after installation, early communication between participants often leads to interface problems during the production, construction, and installation phases. Therefore, participants (designers, manufacturers, and constructors) should be encouraged to participate in collaborative design as early as possible in PBPs [26,70].…”
Section: Trust and Cooperation (Cluster 2)mentioning
confidence: 99%
See 3 more Smart Citations